Toward Greater Social Inclusion in Poland : A Qualitative Assessment in Three Regions - World Bank (Washington, DC, 2014)
In Poland, addressing the situation of the remaining poor groups is likely to become much harder over time as their problems are likely to be deeper and their situation more complex. A social inclusion approach that tackles their multiple disadvantages will be needed. This study aims to contribute to Poland's social inclusion debate by providing policy makers and civil society with evidence from the field about (1) what population groups are currently 'socially excluded;' (2) what are the driving factors of their exclusion; and (3) the success and failure of current social inclusion policies and programs. The ultimate goal of this work is to make current social inclusion interventions more effective by learning from what has been tried. The findings are particularly relevant now that a new EU funding cycle has started, with part of the funds earmarked for tackling social inclusion. The study was conducted in three regions: Malopolskie, Podkarpackie, and Mazowieckie (in Radom County only). The first two are among Poland's poorest regions in terms of income poverty. The part of Mazowieckie in which the research was conducted also has a higher than average poverty rate; in addition, the unemployment rate there (31 percent) is much greater than the national average (about 13 percent in 2013). Capitals of the other two regions were excluded from the research.